Visibility of Chinese ad hoc medical interpreters through text ownership: A case study - Zhang, Wei; Xu, Cui (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Professional interpreters’ visibility in the European context has been widely discussed in the field of community interpreting, but the visibility of untrained ad hoc interpreters in non-European contexts such as China has received little academic attention. By adopting the concept of “text ownership” proposed by Angelelli (2004a), this study examines Chinese ad hoc interpreters’ manifestations of visibility in an authentic medical setting. Based on field observations, audio recordings and interviews, the study reports on four types of visibility demonstrated by ad hoc interpreters: (a) replacing the interlocutor; (b) expressing affect towards a patient; (c) exploring answers; and (d) brokering comprehension. Other forms of visibility are also identified, such as omissions of doctors’ or patients’ remarks and small talk between doctor and interpreter. Interpreters’ deeply held views on social factors as well as the institutional and social norms they have been exposed to are believed to influence their manipulation of medical discourses. This study concludes that in a context where professional medical interpreting services are unavailable, ad hoc interpreters may act as linguistic facilitators by taking on various roles that go beyond mere interpreting. However, their excessive visibility may give rise to potential clinical risks, especially when direct doctor–patient communication is compromised. Attention is drawn to the importance of proper training as well as to the need for the professionalization of medical interpreting in China.